Objektivitas dan Subjektivitas Presentasi Seni - Sudaryanto Sudaryanto (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2004)
Even though the probelms of subjectivity and objectivity in art are not parallel with probelms of form and matter, but there are relationbetween them. The mimesis theory, assuming that art imaitate the nature indicates that the existence of art basiclly convergent with concrete events, while subjective view of art emphasize more on creativity of atmosphere of mind actor.